Religious Moderation In Youtube Content Pemuda Tersesat (Semiotic Analysis Of Habib Husain Ja'far Al-Haddar) - Gandhi, Al Mutia; Zulkarnain, Zulkarnain; Angraini, Angraini; Rahmayani, Nadya (Jurnal Dakwah dan Komunikasi, 2023)
This research focuses on the emergence of messages in the media in the form of religious moderation which aims to provide teaching related to moderation knowledge to viewers who are experiencing a crisis in terms of understanding and implementing religious moderation such as intolerance towards the implementation of other religious worship in the current era. The aim of this research is to find out and understand the concept of religious moderation  in Pemuda Tersesat content. The subject of this research is the Pemuda Tersesat YouTube channel. This research uses Rolland Barthes' semiotic analysis which includes denotation, connotation and myth. The data analysis technique uses qualitative descriptive. Data collection techniques use Library Research and Digital Research. The results of the research show that there is moderation in connotation, denotation and myth. The emergence of moderation varies in media by giving rise to the moderation that exists in today's society. As for religious moderation, in connotation, denotation and myth, there are values of moderation, understanding each other, respecting other people's beliefs, and doing justice to everyone. The emergence of religious moderation has become a middle way for various religious adherents as well as a solution so that every religious community does not have radical and intolerant views.